Majority Rules in Constitutional Referendums. (6th July 2017) - Michel, Stephan; Cofone, Ignacio N.
Summary: The paper addresses the divergence in majority rules at the moment of creating or reforming constitutions. While constitutions require, in most cases, qualified majorities in order to be approved at the constitutional assembly, they normally require only simple majorities to be ratified at the referendum. We analyze the set of conditions under which each majority rule is preferable for constitutional referendums. We argue that the simple majority requirement for referendums in constitution‐making, which is nearly universally used, lacks a clear theoretical justification. Qualified majority rules increase legitimacy and provide additional checks on the drafters. We further highlight when simple majority rules have advantages: when decision‐making costs in the referendum are high. Thereafter, we present an evaluation mechanism to identify the cases in which each majority rule should be used to increase stability and legitimacy. We then apply this evaluation mechanism to the constitution‐making processes in Poland, Bolivia and Egypt, which are three examples of diverging majority rules.